RISE AND FALL OF JACOB ZUMA - Shubin, Vladimir (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
In May 2014 I suddenly received a telephone call from the South African Embassy in Moscow, then an official invitation signed by Jacob Zuma followed: he wanted me to be present at his second inauguration. Unfortunately I failed to do it, I was still recovering from a surgical operation, but the very fact was significant, not because I had been involved, but because it symbolized friendly relations that existed between the South African president and those in Russia who took part in supporting the long struggle against the apartheid regime.